The CLEO RICH detector - Artuso, M; Ayad, R; Bukin, K; Efimov, A; Boulahouache, C; Dambasuren, E; Kopp, S; Li, J; Majumder, G; Menaa, N; Mountain, R; Schuh, S; et al. (2005)
We describe the design, construction and performance of a Ring Imaging Cherenkov Detector (RICH) constructed to identify charged particles in the CLEO experiment. Cherenkov radiation occurs in LiF crystals, both planar and ones with a novel "sawtooth"-shaped exit surface. Photons in the wavelength interval 135-165 nm are detected using multi-wire chambers filled with a mixture of methane gas and triethylamine vapor. Excellent π/K separation is demonstrated. © 2005 Elsevier B.V. All rights reserved.